1996
DOI: 10.1046/j.1365-2621.1996.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

The composition and microbial quality of pre‐packed dates purchased in Greater Glasgow

Abstract: Composition and microbiological contamination was measured in samples of pre-packed dates purchased from a number of stores and retail outlets in Greater Glasgow. The sugar content of dried pitted dates was c. 74%, about 10% more than reported on those packs where nutritional information was given. Potentially pathogenic bacteria like Escherichia coli, Staphylococcus aureus and Bacillus cereus were identified in some of the samples together with lactic acid bacteria, yeasts and moulds, Aspergillus flavus and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 7 publications
(9 reference statements)
5
34
2
Order By: Relevance
“…were detected in almost all the examined date cultivars. Moulds and yeast The results of the present study are in compatibility with those of Aidoo, et al [20] who reported that pre-packed dates purchased in Glasgow contained high levels of coliform, moulds and yeasts and little or very low levels of Staphylococcus aureus. Moisture content is a critical parameter responsible for the microbiological quality of the dates.…”
Section: Microbiological Testssupporting
confidence: 91%
“…were detected in almost all the examined date cultivars. Moulds and yeast The results of the present study are in compatibility with those of Aidoo, et al [20] who reported that pre-packed dates purchased in Glasgow contained high levels of coliform, moulds and yeasts and little or very low levels of Staphylococcus aureus. Moisture content is a critical parameter responsible for the microbiological quality of the dates.…”
Section: Microbiological Testssupporting
confidence: 91%
“…Protein and ash contents were not affected by storage conditions (Table 3). However, a noticeable difference was observed in protein content between the two varieties, which could be due to varietal and origin differences as reported by Aidoo, Tester, Morrison, and MacFarlane (1996).…”
Section: Moisture Protein and Ash Contentsmentioning
confidence: 61%
“…The moisture content was determined by the method described by Shukur (1983). Protein (N×6.25) was determined according to the previous reported method (Aidoo et al 1996). Total lipid and ash contents were obtained by the method given in AOAC (2000).…”
Section: Determination Of Substrate Chemical Compositionmentioning
confidence: 99%